2000
DOI: 10.1086/315223
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Immunodeficiency Virus Type 1 Replication in Human Mononuclear Blood Cells by the Iron Chelators Deferoxamine, Deferiprone, and Bleomycin

Abstract: Replication of human immunodeficiency virus type 1 (HIV-1) can be influenced by iron. Hence, decreasing the availability of iron may inhibit HIV-1 replication. Deferoxamine and deferiprone, both forming catalytically inactive iron-chelator complexes, and bleomycin, by use of which iron catalyzes oxidative nucleic acid destruction, were investigated. Expression of p24 antigen in human monocyte-derived macrophages and peripheral blood lymphocytes (PBL) was reduced by all 3 iron chelators. In PBL, p24 reduction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 41 publications
1
77
0
Order By: Relevance
“…In addition, HIV-1 can induce direct tubular damage, and these changes may affect the tubular reabsorption and/or catabolism of filtered iron containing proteins, leading to the release and accumulation of soluble iron (Fe 2ϩ ) in renal tubules. Soluble iron is able to catalyze the formation of radical oxygen species (ROS) (35)(36)(37)(38)(39) and can also enhance the replication of HIV-1 (40) in macrophages that are recruited to these renal injury sites, causing further renal tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HIV-1 can induce direct tubular damage, and these changes may affect the tubular reabsorption and/or catabolism of filtered iron containing proteins, leading to the release and accumulation of soluble iron (Fe 2ϩ ) in renal tubules. Soluble iron is able to catalyze the formation of radical oxygen species (ROS) (35)(36)(37)(38)(39) and can also enhance the replication of HIV-1 (40) in macrophages that are recruited to these renal injury sites, causing further renal tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that iron enhances hepatitis C virus replication in cultured human hepatocytes (15). Replication of human immunodeficiency virus type 1 can be influenced by iron, as demonstrated by the fact that iron chelators inhibit virus replication (13,32). Iron chelators also inhibit CMV infection and CMV-induced pathogenic changes (20).…”
Section: Vol 75 2001 Notesmentioning
confidence: 99%
“…To investigate whether the sHZmediated up-regulation of IFN-␥-inducible NO synthesis was simply an effect of HZ iron, B10R M were treated for 1 h with increasing 100 -400 M doses of desferrioxamine (DFX), a commonly used iron chelator (35). Then, IFN-␥ Ϯ sHZ were added and nitrite production was monitored after 24 h. As shown in Fig.…”
Section: The Synergistic Effect Of Shz On Ifn-␥-dependent No Inductiomentioning
confidence: 99%